Peran Masyarakat Nusantara dalam Konstruksi Kawasan Asia Tenggara Sebagai Poros Maritim Dunia pada Periode Pramodern - Singgih Tri Sulistiyono; Yety Rochwulaningsih; Haryono Rinardi (Department of History, Faculty of Humanities, Diponegoro University, 2020)
The main objective of this article is to trace the pioneering role that might be played by the ancestors of the Indonesian people, Malay-Austronesian, in constructing the Southeast Asian region as a world maritime fulcrum in the pre-modern period. It is very important to be studied considering the fact that until now the historiography of both Indonesia and Southeast Asia still pays little attention to the role of Southeast Asia people in establishing the glory of Southeast Asia as one of the world's maritime axis. That is why their role needs to be elaborated more deeply by exploring broader literature and historical sources. Likewise, a new perspective also needs to be developed to build a narrative of the role of local communities in the process of globalization in the region. For this purpose, this article explains how Indonesian ancestors became the decisive pioneers in the reconstruction of the Southeast Asian region as one of the centers of world maritime activity.